A Better Understanding of Diethylstilbestrol Electro‐oxidation: Towards the Design of an Electrochemical Sensor. Issue 4 (2nd December 2020) - Bibani, Malek; Ktari, Nadia; Fourati, Najla; Zerrouki, Chouki; Kalfat, Rafik
Abstract: The obstacle for the development of a reliable electrochemical technique to trace diethylstilbestrol (DES) lies in the complex electrochemical behavior of this illicit hormone. The present study targeted to thoroughly investigate and understand the electro‐oxidation of DES in acetonitrile on gold electrode by cyclic voltammetry (CV) and square wave voltammetry (SWV) techniques. DES voltammogram has shown two anodic peaks, implicating two successive and irreversible processes. Adsorption and diffusion properties were studied and characterized using electrochemical, spectroscopic and morphological techniques. Avoiding adsorption, and under diffusion process only, a good linear correlation between peak current and DES concentration in the range of 0.25 to 1000 μmol/L was obtained with a detection and quantification limits of 0.2 μmol/L and 0.7 μmol/L, respectively, and a sensitivity of 0.016 A/mM. Competitivity tests, between DES and its structural analog hexestrol (HS), were carried out by chronoamperometry and SWV. HS even added in excess was found to merely affect DES electrochemical measurement. The established method exhibited high precision and reproducibility, and allows the easy and successful determination of DES in poultry feed sample. With a deep insight into its complex electrochemical behavior, this work paves the way to the development of selective, sensitive and easy‐to‐use electrochemical sensors directed towards this synthetic hormone and the related chemicals such as phenolic compounds. Abstract :